Missing: A Detective Ravn thriller - Krefeld, Michael Katz (Saga Egmont, 2024)
One missing person. Endless buried secrets... When a man vanishes after embezzling funds for a secret rendezvous in Berlin, Ravn is drawn into a chilling investigation by the man\'s sister, Louise. The mystery deepens as Ravn discovers a pattern of lonely men disappearing under mysterious circumstances, a trail leading back to the dark days of Stasi-Germany. As he gets closer to the truth, Ravn finds himself caught in the crosshairs, stirring up horrors better left buried... The gripping second book of Michael Katz Krefeld\'s acclaimed “Ravn” series, “Missing” is a pulse-pounding thriller from the Danish crime master that will leave you on the edge of your seat. Fans of Jo Nesbø and Peter Høeg will love this gritty, Nordic Noir series. Detective Ravn Thrillers In the thrilling Nordic noir series, ”Detective Ravn”, Thomas \"Raven\" Ravnsholdt, a tenacious private detective, navigates the dark underbelly of society. Ravn\'s investigations take him through a chilling labyrinth of crime, encountering trafficking rings, rampant corruption, doomsday cults, and haunting relics from the GDR era. Fans of Scandinavian crime thrillers, will love this Danish detective series in English for the first time. Perfect for readers of Jo Nesbø, Stieg Larsson, and Peter Høeg. Best-selling Danish crime author Michael Katz Krefeld is renowned for his Nordic Noir series featuring Detective Ravn. His gripping, fast-paced crime thrillers explore personal sacrifice and the fight against evil, all set against the atmospheric backdrop of Scandinavia.